2012
DOI: 10.1097/pas.0b013e31824324e6
|View full text |Cite
|
Sign up to set email alerts
|

The 3-layered Ductal Epithelium in Gynecomastia

Abstract: Gynecomastia is the most common abnormality in the male breast and has been associated with male breast cancer, but whether there is an etiological role remains unknown. In the present study we conducted an immunohistochemical investigation to further characterize gynecomastia. A total of 46 cases of gynecomastia were immunohistochemically stained on tissue microarrays for estrogen receptor (ER), progesterone receptor, HER2, androgen receptor, cytokeratins (CK5, CK14, CK7, and CK8/18), p63, E-cadherin, BRST2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Gynaecomastoid hyperplasia was identified in 47.9% (34/71) of all the specimens. Morphologically it demonstrated ducts surrounded by an outer layer of myoepithelial cells with expression of CK5/6, an intermediate layer of cuboidal-to-columnar, vertically oriented cells expressing ER but not CK5/6, and an inner layer of slightly smaller luminal cells with or without micropapillae formation and these cells express CK5/6 consistently but ER only rarely 27. Thus this can be differentiated from the lesional foci basing on morphology and immune-phenotypic profile.…”
Section: Discussionmentioning
confidence: 89%
“…Gynaecomastoid hyperplasia was identified in 47.9% (34/71) of all the specimens. Morphologically it demonstrated ducts surrounded by an outer layer of myoepithelial cells with expression of CK5/6, an intermediate layer of cuboidal-to-columnar, vertically oriented cells expressing ER but not CK5/6, and an inner layer of slightly smaller luminal cells with or without micropapillae formation and these cells express CK5/6 consistently but ER only rarely 27. Thus this can be differentiated from the lesional foci basing on morphology and immune-phenotypic profile.…”
Section: Discussionmentioning
confidence: 89%
“…However, such ducts were also seen in gynaecomastia (florid type), as has been recognized previously . Further, these ducts showed immunohistochemically the three layers that are typical of gynaecomastia: CK5/6‐ and CK14‐positive and ER‐negative outer myoepithelial and inner luminal layers, and an ER‐positive and CK5/6‐ and CK14‐negative intermediate layer …”
Section: Discussionmentioning
confidence: 95%
“…Since male breast cancer is often diagnosed together with gynecomastia, although gynecomastia is not an obligate precursor of male breast cancer [28], we examined whether the expression of the selected membrane markers was specific for male breast cancer. We found that expression patterns in gynecomastia were largely comparable with normal female breast tissue; i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Original HE slides were reviewed by two observers (PJvD, RK) to confirm the diagnosis, and to subtype gynecomastia (florid, intermediate, fibrous) as described before [28]. Tissue microarrays were constructed as described by Kornegoor et al [7], [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation